The Effect of Polymer-Fiber Stabilization on the Unconfined Compressive Strength and Shear Strength of Sand - Jin Liu; Qiao Feng; Yong Wang; Yuxia Bai; Jihong Wei; Zezhuo Song (Advances in Materials Science and Engineering)
The mixed soil stabilizer of polyurethane organic polymer and polypropylene fiber was used to reinforce sand. The unconfined compressive test and direct shear test were carried out to evaluate the effects of polymer-fiber reinforced sand. The different contents of polymer and fiber were selected for the tests. The test results indicated that polymer-fiber mixture can improve strongly the strength of sand. The presence of polyurethane organic polymer enhances sand structural stability and the best composition of polymer and fiber was 4% and 0.2–0.3% of dry sand, respectively. Based on the test results and images of scanning electron microscope (SEM), the reinforcement mechanism was analyzed. The research results can be considered as the reference for sand reinforced engineering.